Optimization of an Operation Mode of the Solid-State Image Sensor in a Short-Wave Infrared Region - D. A. Belous (Известия высших учебных заведений России: Радиоэлектроника)
Increase in quantum efficiency of silicon image sensor in the short-wave infrared range 900…1100 nm is shown theoretically and confirmed experimentally in case of temperature increase of a crystal. This increase is caused by reduction of width of the forbidden band of silicon in case of temperature increase of a crystal from +50 °C to +130 °C. The experimental study of the dark currents showed that for CMOS-sensors of Sony their value anomally small up to temperature of +130 °C. Thus, optimization of temperature of a crystal of the image sensor by criterion of the relation signal/noise is possible. It is set that in case of temperature increase of a crystal to +80 °…+120 °C the relation signal/noise by operation on wavelength of 1064 nanometers increases in 2 … 3 times.